The effect of profitability and liquidity on the value of companies with capital structure as an intervening variable - Mukhtaro, Hidayatul; Apriyanto, Gaguk; Respati, Harianto (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
This research aims to describe profitability, liquidity, capital structure, and firm value; analyze the influence of profitability on capital structure; analyze the influence of liquidity on capital structure; analyze the influence of profitability on firm value; analyze the influence of liquidity on firm value; analyze the influence of capital structure on firm value; analyze the indirect effect of profitability on firm value through capital structure; and analyze the indirect effect of liquidity on firm value through capital structure. The population in this study consists of 27 listed companies. The sampling technique used is purposive sampling with criteria that provide financial reports for 4 years, from 2019 to 2022. Based on these criteria, a total of 13 companies were selected as samples. The data analysis technique used is path analysis. The results of the analysis show that profitability has a significant influence on capital structure. However, liquidity does not have a significant influence on capital structure. Profitability does not have a significant influence on firm value, whereas liquidity has a significant influence on firm value. Capital structure does not have a significant influence on firm value. Additionally, profitability does not have an indirect influence on firm value through capital structure, and neither does liquidity.